PEMANFAATAN TANNIN KULIT KAYU AKASIA UNTUK PENGAWETAN JATI PUTIH (Gmelina arborea) TERHADAP RAYAP TANAH (Coptotermes curvignathus holmgren) - Niken Pujirahayu; zakiah Uslinawati; Nurhayati Hadjar (Jurnal Ecogreen, 2015)
The aim of the reserach was to determine the antitermite properties of bark extract of mangium (Acacia mangium) on Gmelina wood (Gmelina arborea) and determine the optimum concentration levels and immersion duration. The research scheme applied completely randomized design, treatment is done factorially with 2 factor treatments. The first factor is concentration levels of bark extract (7 % , 5 % and 3 %). The second factor is immersion duration in preservative material are 24 hours, 48 hours, and 72 hours. The test done with feeding test. The parameter which was observed namely: retention of mangium bark extract and weigh loss of gmelina wood.  Result showed that the higest retention  found on 7 % concentration levels and  48 hours immersion (3,75 kg/m 3).  The lowest wood sample weight loss found at concentration  7 % and 24 hours immersion (19,31 %). Keywords : bark extract, Acacia mangium, Gmelina arborea, retentions